BUKHARA REGIONAL COLLECTOR – FUNDAMENTAL OF OPTIONAL OPTIONS FOR USE OF EXCAVATORS FOR CLEANING DRINKS - Makhmudova Maftuna Maqsud qizi; Sobirov Komil Sodiq uglu; Ergashev Saidolim Inomjon uglu (Galaxy International Interdisciplinary Research Journal, 2022)
The article contains excavators in Bukhara region and their optimal options for the selection of excavators, taking into account their hydraulic parametrs and the importance of collectors- ditches, as well as the timely completion of work on its cleaning and reconstruction. Substantiation using formulas. Its also provides advice on the effective use of existing excavators.